2008
DOI: 10.3846/1648-7788.2008.12.66-79
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Non-Linear Analysis of a Cracked Blade

Abstract: A cracked blade non-linear dynamic analysis was performed, taking into account contact interaction between crack sides. The contact-induced non-linear problem was solved by using the harmonic balance method. Accuracy and computational efficiency are demonstrated by comparing the results with the time integration of the system's motion equation Problem size reduction was performed using system fixed-interface method. They suppose that a crack forms an interface between two sub-structures and use a relative degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In [24], a crack was equivalent to the change of local stiffness and then a nonlinear amplitude-dependent function was used to model a breathing crack. In addition, contact-based two-dimensional finite element models have already been studied to model breathing cracks [19,[25][26][27]. So it can be summarized that traditional nonlinear dynamic analysis of a blade with a breathing crack is mainly based on vibration displacements, which has been testified to be much effective for large cracks.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], a crack was equivalent to the change of local stiffness and then a nonlinear amplitude-dependent function was used to model a breathing crack. In addition, contact-based two-dimensional finite element models have already been studied to model breathing cracks [19,[25][26][27]. So it can be summarized that traditional nonlinear dynamic analysis of a blade with a breathing crack is mainly based on vibration displacements, which has been testified to be much effective for large cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [16] stated that the nonlinearity due to the crack closing effect has to be considered for the in-plane bending case but crack closing was neglected in their study because their work focused on the out-of-plane bending vibration. Reference [17] simulated a dynamic model for cracked blade on periodically varying load. They concluded that the assumption of linear (open) crack is not real and he showed that there was a distinct difference in amplitudes for linear and nonlinear cracked blades.…”
Section: Introductionmentioning
confidence: 99%